Pengembangan alat uji impak charpy di bagian pengereman, berat pendulum, dan skala ukur pada mesin impak charpydi Laboraturium Teknik Mesin Unhasy - Adi, Budi Prasetyo; Irfa`i, Muhammad Arif; Rosadi, Muhammad Munib (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2020)
The impact test is a test to determine the strength of the material when receiving a load constantly or suddenly. The previous tool did not meet the test requirements, so it required the development of the pendulum weight sector, the measuring scale and the addition of a braking system. Therefore, this research was carried out for the development of previous tools so that the test tools could meet the requirements and the testing of the tools using ST 41 and ST 60 carbon steel specimens. This research is a research and development study using ADDIE (analysis, design, development, implementation and evaluation) as a reference in conducting research. The development of the tool focuses on the pendulum weight to 10.2 kg, replacing the measuring scale and adding a braking system that uses disc brakes. The results of the expert validation questionnaire got a score of 72.63%, the small respondent data questionnaire got a score of 83% and the large-scale respondents got a score of 85%. This shows that the tool gets a decent score. The results of the performance test of the tool using ST 41 carbon steel with an average impact price of 1.02302732 J / mm and carbon steel ST 60 with an average impact price of 1.2422299 J / mm. This study shows that there is an average difference in the impact price between ST 41 carbon steel and ST 60 carbon steel as indicated by the Sig. (2-tailed) value of 0.484 using independent sample test T-test data processing.